1978
DOI: 10.1083/jcb.77.1.246
|View full text |Cite
|
Sign up to set email alerts
|

Structure of interphase nuclei in relation to the cell cycle. Chromatin organization in mouse L cells temperature-sensitive for DNA replication

Abstract: Mutant lines of mouse L cells, TS A1S9, and TS C1, show temperature-sensitive (TS) DNA synthesis and cell division when shifted from 34 ~ to 38.5~ With TS A1S9 the decline in DNA synthesis begins after 6-8 h at 38.5~ and is most marked at about 24 h. Most cells in S, G~, or M at temperature upshift complete one mitosis and accumulate in the subsequent interphase at G~ or early S as a result of expression of a primary defect, failure of elongation of newly made small DNA fragments. Heat inactivation of TS C1 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

1978
1978
1993
1993

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…It has long been acknowledged that changes in the metabolic status of the nucleus, whether a result of differentiation [11,24], activation [10,13,14,28,53,54] or pathogenesis induced by mutation [52], drugs [9,23,33,48], virus infection [12,18] or malignancy [25], have profound effects on nuclear organization. Alterations in nuclear structure have generally been defined by differences in nuclear size and shape, extent of nucleolar development, and the state of chromatin aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been acknowledged that changes in the metabolic status of the nucleus, whether a result of differentiation [11,24], activation [10,13,14,28,53,54] or pathogenesis induced by mutation [52], drugs [9,23,33,48], virus infection [12,18] or malignancy [25], have profound effects on nuclear organization. Alterations in nuclear structure have generally been defined by differences in nuclear size and shape, extent of nucleolar development, and the state of chromatin aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Newly replicated chromatin is probably unfolded (12,(24)(25)(26). As histone Hi is present very early during chromatin replication, it seems likely that further chromatin folding during the maturation process involves additional interactions between the linker DNA and the core histones and interactions between histone molecules of neighboring nucleosomes.…”
Section: Discussionmentioning
confidence: 99%
“…The higher order structure of newly replicated chromatin is probably unfolded (12,(24)(25)(26). Maturation of newly replicated chromatin is suggested to be mediated by histone Hi, which is known to play an important role in organization of the chromatosome and of the higher order structures of chromatin (27).…”
mentioning
confidence: 99%
“…7; unpublished data), which revealed that the chromatin-bound DNA is rendered inactive as an in situ template for replication, as a result of heat denaturation of the ts A1S9 gene product. These findings, and others which indicated that expression of the ts AlS9 defect results in modification of chromatin structure (8) and supercoiling of the nuclear DNA (9), suggested that the ts AlS9 mutation may affect a protein which determines DNA conformation-i.e., a topoisomerase.…”
mentioning
confidence: 98%